Understanding heterogeneity: A mixed-method analysis to inform context-specific strategies for the inclusive scaling of improved bean varieties - Quintero, Katherine; Pérez, Yuliana; Taborda, Luis; Pérez, Salomón; Morales, Herlindo; Buritica, Alexander; Vargas, Sandra; González, Carolina; Jiménez, Luz Adriana; Reyes, Byron (2025)
This study, prepared for the Scaling for Impact Science Program of the CGIAR, analyzes producer typologies and value-chain barriers affecting adoption of improved and biofortified common bean varieties in Guatemala to inform context-specific scaling strategies. Using a mixed-methods design, it combines factorial analysis of mixed data and hierarchical clustering of a survey of 516 producers with thematic and semantic clustering analyses of 12 semi-structured interviews with institutional actors. At the farmer level, three typologies were identified: young female subsistence farmers, middle-aged indigenous male subsistence farmers, and older male market-oriented farmers, differing in assets, technology access, and market engagement. At meso and macro levels, six thematic areas shape adoption, including market dynamics, institutional governance, and sociocultural factors. Scaling implications vary by typology, requiring gender-sensitive and culturally adapted extension, differentiated finance and risk-management mechanisms, and strengthened market linkages. Cross-cutting needs include inclusive communication, intergenerational learning, and outreach to remote areas. At higher levels, effective scaling depends on institutional coordination for strategic seed stocks, locally validated varieties, demonstration plots, demand-side linkages to institutional buyers, and consumer-oriented approaches integrating nutritional and sensory preferences.